Serum CD5L predicts acute lung parenchymal injury and acute respiratory distress syndrome in trauma patients. Issue 39 (1st October 2021) - Cheng, Qian; Lai, Xiaofei; Yang, Liping; Yang, Huiqing; Luo, Yan
Abstract : Abstract: Cluster of differentiation 5 antigen-like (CD5L), derived from alveolar epithelial cells partly, is a secreted protein. It is shown that CD5L is associated with lung inflammation and systemic inflammatory diseases, but the relationship between CD5L and trauma-related acute lung parenchymal injury (PLI), acute lung injury or acute respiratory distress syndrome (ARDS) is unclear. This study aims to explore the value of serum CD5L levels in predicting trauma-associated PLI/ARDS and its potential clinical significance. This is a prospective observational study, and a total of 127 trauma patients were recruited from the emergency department (ED), and among them, 81 suffered from PLI/ARDS within 24 hours after trauma, and 46 suffered from trauma without PLI/ARDS. Fifty healthy subjects from the medical examination center were also recruited as controls for comparison. The serum CD5L level was measured within 24 hours of admission. The receiver operating characteristic analysis and logistic regression analysis were used to identify the correlation between high CD5L and trauma associated-PLI/ARDS within 24 hours following trauma. The trauma associated-PLI/ARDS subjects showed a significantly higher level of serum CD5L on emergency department admission within 24 hours after trauma compared with its level in non-trauma associated-PLI/ARDS subjects and healthy subjects. The initial CD5L concentration higher than 150.3 ng/mL was identified as indicating a high risk of PLI/ARDS within 24 hours following trauma (95% confidence interval: 0.674–0.878; P  < .001). Moreover, CD5L was an independent risk factor for trauma associated-PLI/ARDS within 24 hours following trauma. CD5L could predict PLI/ARDS within 24 hours following trauma.